2012
DOI: 10.1002/rcm.6227
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation of the food dye Brilliant Blue in aqueous medium: monitoring and characterization of products by direct infusion electrospray ionization coupled to high‐resolution mass spectrometry

Abstract: A greater ecotoxicity against Artemia salina was observed for the by-products than for the original dye. This indicates that the identification of by-products arising from oxidation treatments is of primary importance since such compounds can be more hazardous than the precursor itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Another intermediate produced was formed by the loss of an N ‐methylbenzenesulfonic acid group (MBSA). In the case of brilliant blue FCF ozonation, Silva et al reported four by‐products, all of which were produced by initial attack of oxy‐radicals on the BB‐FCF dye N ‐amino benzyl groups.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Another intermediate produced was formed by the loss of an N ‐methylbenzenesulfonic acid group (MBSA). In the case of brilliant blue FCF ozonation, Silva et al reported four by‐products, all of which were produced by initial attack of oxy‐radicals on the BB‐FCF dye N ‐amino benzyl groups.…”
Section: Introductionsupporting
confidence: 71%
“…In all cases, hydroxyl (OH) and superoxide anion (O 2 − ) radicals, extremely reactive owing to their high oxidation potentials, are responsible for dye degradation, resulting in simpler organic compounds or complete mineralization into inorganic substances . These unstable radicals are products of the reaction of electrons and holes created by the UV on the TiO 2 with absorbed water and oxygen molecules . The dye structures and chemical functional group reactivity strongly influence these decomposition processes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Most conventional treatment processes do not allow complete degradation of molecules containing azo structures, and may even lead to the formation of secondary compounds of higher toxicity. [7,11] On the other hand, advanced oxidative processes are very effective methods for the degradation of toxic and biologically recalcitrant pollutants. These processes are distinguished by the formation of several free radicals, especially hydroxyls, which are known by their oxidizing power and, through a non-selective reaction, can lead to the complete mineralization of organic pollutants.…”
mentioning
confidence: 99%
“…In view of this situation, the main ESI‐MS fragmentation mechanisms of a series of antitumor agents containing the tetrahydroquinoline scaffold, which included eight furo[3,2‐ c ]tetrahydroquinoline and six pyrano[3,2‐ c ]tetrahydroquinoline derivatives (Tables and ), were investigated. First, moderate‐resolution and accurate mass measurements were achieved with an ESI‐Q‐TOF mass spectrometer to acquire the elemental compositions of the fragment ions . Second, multistage electrospray ionization (ESI‐MS n ) experiments in an ion trap instrument allowed us to understand the relationship between precursor and product ions .…”
Section: The Structures and Main Fragmentation Pathways Of Furo[32‐cmentioning
confidence: 99%